The Influence of Transformational Leadership and Compensation on Sustainable Employee Performance Mediated by Work Motivation (Study of Pt. Sumber Indah Lestari) - Krisnawan, Dwi (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aims to examine and analyze the influence of transformational leadership and compensation on sustainable employee performance, with work motivation serv-ing as a mediating variable, in the context of PT. Sumber Indah Lestari. A quantita-tive approach was employed using Structural Equation Modeling–Partial Least Square (SEM-PLS) as the analytical method. Data were gathered through question-naires distributed to 150 store leaders (firstmen) who participated as respondents. The findings indicate that transformational leadership has a positive and significant impact on work motivation and directly affects sustainable employee performance. Compensation also demonstrates a significant influence on work motivation, but does not have a direct significant effect on sustainable performance. However, work motivation is proven to significantly mediate the relationship between both trans-formational leadership and compensation with sustainable employee performance. These results highlight the importance of inspirational, supportive, and visionary leadership, reinforced by a fair and transparent compensation system that aligns with employee contributions. The managerial implications of this research empha-size the need to strengthen transformational leadership practices at the operational level and to review and improve compensation systems to better motivate employees and enhance long-term productivity. Furthermore, this study contributes to the theo-retical development of sustainable employee performance, particularly in the mod-ern retail sector in Indonesia, by integrating motivation as a key mediating factor in organizational performance strategies.